(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The dynamics of word-types and subtypes composite-suffixed nouns description for a locative and supporting substantive and verbal fundamentals new Ukrainian language late XVII – early XXI c.